Effect of arterial oxygen desaturation on six minute walk distance, perceived effort, and perceived breathlessness in patients with airflow limitation. Issue 1 (January 1993) - Mak, V H; Bugler, J R; Roberts, C M; Spiro, S G
Abstract : BACKGROUND: The effect of exercise induced hypoxaemia in determining submaximal exercise capacity, perceived breathlessness, and perceived exertion is not known. The purpose of this study was to investigate the relation of these variables to the results of lung function tests and the degree of hypoxaemia during submaximal exercise in patients with airflow limitation. METHODS: Forty two patients with chronic obstructive airways disease and 28 patients with chronic severe asthma were studied. Spirometry was performed and gas transfer (TLCO) and lung volumes were measured. Submaximal exercise capacity was assessed with a standardised six minute walk test. Arterial oxygen desaturation during the walk test was monitored by a portable pulse oximeter. Patients rated their perceived degree of respiratory impairment on a Medical Research Council (MRC) breathlessness scale before the walk. Perceived breathlessness was measured by means of a linear visual analogue scale and exertion on the Borg scale after the walk. RESULTS: The six minute walk distance was strongly correlated (r value) with TLCO (0.68), peak expiratory flow (PEF: 0.55), forced expiratory volume in one second (FEV1: 0.53), transfer coefficient KCO: 0.49), age (-0.49), and forced vital capacity (FVC: 0.48) but not with oxygen desaturation during the walk. Walk distance was also correlated with the breathlessness rating on the MRC scale (-0.52), but less strongly with perceived breathlessness (-0.35) and perceived exertion (-0.30). The prediction equation for the six minute walk distance in metres (6MD) generated by multiple regression analysis was 6MD = 387 + 29.7 (TLCO) -3.1 (age) + 0.35 (PEF 1/min), which accounted for 50% of the total variance in walk distance. The mean level of saturation during the walk correlated most significantly with TLCO (0.55), FEV1/FVC (0.54), and PEF (0.48), but not with walk distance or with the rating on any of the analogue scales. The prediction equation produced by multiple regression analysis for the mean level of saturation during the walk was MEANSAT(%) = 1.3(TLCO) + 1.5 (base-line saturation) - 0.01 (6MD) - 54. CONCLUSIONS: Oxygen desaturation during the six minute walk is not related to walk distance, nor does it determine the degree of perceived exertion or perceived breathlessness in patients with airflow limitation. Patients who consider themselves the most disabled by breathlessness have the shortest six minute walk distance but do not necessarily have appreciable desaturation.